Treatment of primary hepatic neuroendocrine tumors with associating liver partition and portal vein ligation for staged hepatectomy (ALPPS): A case report and literature review. Issue 37 (September 2018) - Qu, Chao; Qu, Lin-lin; Zhu, Cheng-zhan; Wang, Zu-sen; Cao, Jingyu
Abstract: Rationale: Primary hepatic neuroendocrine tumors (PHNETs) are extremely rare and are difficult to diagnose preoperatively.We report a case of PHNET diagnosed preoperatively and successfully resected using associating liver partition and portal vein ligation for staged hepatectomy (ALPPS). Patient concerns: A 72-year-old woman was admitted to our hospital for a hepatic mass, which was incidentally identified during a routine health checkup. The patient has no other obvious symptoms of discomfort. Diagnoses: Physical examination revealed a palpable mass in the right upper quadrant of her abdomen. Dynamic contrast-enhanced abdominal computed tomography (CT) showed a low-density mass measuring 13 × 7 × 6 cm in both, the right and left hepatic lobes. 18 F-fluorodesoxyglucose positron emission tomography ( 18 F-FDG PET) and fused PET/CT showed increased uptake by the mass, which was indicative of a hepatic tumor. Interventions: We use a novel ALPPS surgical procedure to safely and radically remove primary neuroendocrine tumors. Outcomes: No postoperative bleeding and bile leakage were reported, and the patient recovered uneventfully.The patient was followed-up for a year without recurrence. Lessons: PHNETs are rare tumors, and confirming the diagnosis using the best possible preoperative examination is important. An optimal treatment plan is selected based on the patient's condition to ensure a favorable prognosis. Tumors too large to undergo surgical removal can be resected using the ALPPS procedure, as described in this case report.